2008
DOI: 10.1021/jm7010657
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of 4-Aryl-4H-chromenes as a New Series of Apoptosis Inducers Using a Cell- and Caspase-Based High Throughput Screening Assay. 4. Structure–Activity Relationships of N-Alkyl Substituted Pyrrole Fused at the 7,8-Positions

Abstract: In our continuing effort to discover and develop apoptosis inducing 4-aryl-4H-chromenes as novel anticancer agents, we explored the structure-activity relationship (SAR) of alkyl substituted pyrrole fused at the 7,8-positions. A methyl group substituted at the nitrogen in the 7-position of the pyrrole ring led to a series of potent apoptosis inducers with potency in the low nanomolar range. These compounds were also found to be low nanomolar or subnanomolar inhibitors of cell growth, and they inhibited tubulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
68
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 188 publications
(72 citation statements)
references
References 17 publications
1
68
0
Order By: Relevance
“…Searching the literature revealed the outstanding activity of 4-aryl-4H-chromenes as apoptotic inducers and cytotoxic agents. Thus, 4-aryl-4H-chromenes (like compounds IV and V) were reported as potent apoptosis inducer in human breast cancer cells T47D [18][19][20] . Their SAR study indicated that both the 2-amino and the 3-cyano groups were essential for the antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Searching the literature revealed the outstanding activity of 4-aryl-4H-chromenes as apoptotic inducers and cytotoxic agents. Thus, 4-aryl-4H-chromenes (like compounds IV and V) were reported as potent apoptosis inducer in human breast cancer cells T47D [18][19][20] . Their SAR study indicated that both the 2-amino and the 3-cyano groups were essential for the antitumor activity.…”
Section: Introductionmentioning
confidence: 99%
“…Their SAR study indicated that both the 2-amino and the 3-cyano groups were essential for the antitumor activity. Replacement of the cyano with ester group or replacement of the amino with amide or urea groups decreased the antitumor activity 19,20 .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, two major classes of small molecular compounds inducing apoptosis have been developed as potential anticancer agents, including the caspase-inhibiting isatin derivatives [113][114][115] and the apoptosis-inducing 4-aryl-4H-chromens, which inhibit tubulin polymerization and bind at the colchicine binding site [115][116][117]. Several articles have reported the synthesis and biological evaluation of radiolabeled isatin derivatives for imaging of apoptosis using PET [114,[118][119][120][121][122][123].…”
Section: Apoptosis Pet Imaging For Cancer Therapy Responsementioning
confidence: 99%
“…Some hemiaminals of indole and related N-heterocycles possess anti-tumor activity (2,3). Additionally, these compounds have been utilized as labile precursor for in-situ generation of formaldehyde (4Á6) and a selfcleavable linker for drug molecules to improve their bioavailability (7,8).…”
Section: Introductionmentioning
confidence: 99%